Protocol: action planning for action research about kaizen in public organizations. The case of higher education - Juan A. Marin-Garcia; Julio J. Garcia-Sabater; Julien Maheut (WPOM : Working Papers on Operations Management)
In this protocol we complete the first three stages of action research to analyze possibilities for continuous improvement of processes in public universities. We define the problem or area of improvement in the organization; we identify the relevance of the topic to generate an academic contribution and propose an action plan or work protocol. Although we have focused on a public higher education organization, this protocol can be applicable without requiring too many adaptations, to any public service (at least in the Spanish context).